Improving the operational skills of the health personnel working in the emergency departments. (13th November 2019) - Arnone, R; Romano, G; Skinner, J; Watt, S; Poenicke, C; Hoestergard, D; Chiaramonte, G
Abstract: : In December 2013 the European Commission approved the project promoted by CEFPAS, The Centre for Training and Research in Public Health within the programme PROGRESS, "Improving the operational skills of health personnel working in the emergency departments. A useful tool to give concrete answers to EU policies on patients' safety and to create new working opportunities". This project aimed to combine the need to find innovative solutions in the field of healthcare with the objective of increasing the safety of patients in emergency departments, while also covering the need to promote worker mobility within the European Union. The key tool for implementing this goal is the exchange of experience and best practices. The project partners included: the Edinburgh University of Medicine, the Napier University (again in Edinburgh), the Dresden University of Technology, the Herlev Hospital (in Copenhagen) through the DIMS or the Danish Institute for Medical Simulation at the University of Copenhagen, as well as ISMETT and CREAM (the Research Centre of the University of Medicine) in Palermo. Every partner, during the planning, has provided the know how developed in the area of emergency. Specifically it has been analyzed the possibility to compare and visit the simulation Centres of Edinburgh, Dresden and Palermo, and to study the use, in each country, of innovative methodology during the training of the health personnel. The partner, during the planning of the project, studied also how to help people to find easier jobs opportunities in the health sector (so they thought to create a specific data base of the emergency departments operating in Italy, Scotland and Germany where to find a job or a chance for an internship). The project has lasted for one year and has provided research activities and the exchange of experience and best practices. Key messages: There is a huge difference regarding the way in which the emergency system is organized within single countries around Europe. Comparing high-level organisations we have benefited in terms of ideas, projects and potential objectives to be set in order to improve our work and to improve results for patients.